Pediatric Rib Fractures Identified by Chest Radiograph: A Comparison Between Accidental and Nonaccidental Trauma. Issue 12 (5th December 2021) - Ruest, Stephanie; Kanaan, Ghid; Moore, Jessica L.; Goldberg, Amy P.
Abstract : Supplemental digital content is available in the text. Abstract : Objective: The objective of this study was to determine the prevalence of rib fractures (RFs) identified by chest x-ray (CXR) among children younger than 2 years who sustained accidental versus nonaccidental injuries. It is hypothesized that RFs are uncommon among all accidental pediatric trauma mechanisms (eg, falls, motor vehicle crashes) as compared with the prevalence of RFs in the setting of nonaccidental trauma (NAT). Methods: A retrospective chart review of sequential CXRs of children younger than 2 years evaluated at a pediatric level 1 trauma center for accidental trauma and possible NAT was conducted from January 1, 2011, to October 31, 2016. Data collected included demographics, CXR indication and findings, history of cardiopulmonary resuscitation, trauma mechanism, associated injuries, final diagnoses, and outcomes. Results: Two (<1%) of 226 CXRs obtained to evaluate accidental trauma demonstrated acute RFs. Ten (19.6%) of 51 CXRs obtained in the setting of concern for NAT revealed RFs (9/10 identified only healing RFs and 1/10 identified acute RFs). Among patients with a final diagnosis of NAT (ie, not neglect, accidental trauma, etc; n = 38), the overall prevalence increased to 26.3%. Conclusions: The presence of RFs in pediatric accidental trauma is uncommon even in the setting of high-force mechanisms, and when identified, these RFs are acute. Comparatively, the overall prevalence of RFs identified on CXR among cases with a final diagnosis of NAT was much higher and almost exclusively healing RFs. These data provide support that identification of RFs is highly concerning for NAT even if an accidental mechanism is provided. When RFs are identified, a full NAT work-up should be considered.